Another mouse to feed - Kraus, Robert (New York : Simon & Schuster Books for Young Readers, 1980)
When Mr. and Mrs Mouse became exhausted from overwork caring for their many children, the little mice decide to take over.
Keywords: Mice - Fiction; Parent and child - Fiction